Disposal Of Solid Domestic Waste Produced by The Population - Department Assistant: Saidova S.A; Turg‘unova Zarnigorxon Zohidjon qizi; Ibrohimova Yulduz Baxodir qizi (Zien Journals, 2022)
The environment has always been a source of resources for mankind, but for a long time its life activity did not have a significant impact on nature. 'y began to give.
Keywords: Processing; disposal; bacteria; environment